Indole-3-Carbinol (I3C) Protects the Heart From Ischemia/Reperfusion Injury by Inhibiting Oxidative Stress, Inflammation, and Cellular Apoptosis in Mice - Li, Qi; Xia, Boyu; Wu, Jingjing; Yuan, Xiaomei; Lu, Xu; Huang, Chao; Gu, Hongcheng; Zheng, Koulong; You, Qingsheng; Liu, Kun (Frontiers in Pharmacology, 2022)
Strategies for treating myocardial ischemia in the clinic usually include re-canalization of the coronary arteries to restore blood supply to the myocardium. However, myocardial reperfusion insult often leads to oxidative stress and inflammation, which in turn leads to apoptosis and necrosis of myocardial cells, for which there are no standard treatment methods. The aim of this study was to determine the pharmacological effect of indole-3-carbinol (I3C), a phytochemical found in most cruciferous vegetables, in a mouse model of myocardial ischemia/reperfusion injury (MIRI). Our results showed that I3C pretreatment (100 mg/kg, once daily, i. p.) prevented the MIRI-induced increase in infarct size and serum creatine kinase (CK) and lactate dehydrogenase (LDH) in mice. I3C pretreatment also suppressed cardiac apoptosis in MIRI mice by increasing the expression levels of the anti-apoptotic protein Bcl-2 and decreasing the expression levels of several apoptotic proteins, including Bax, caspase-3, and caspase-9. In addition, I3C pretreatment was found to reduce the levels of parameters reflecting oxidative stress, such as dihydroethidium (DHE), malondialdehyde (MDA), reactive oxygen species (ROS), and nitric oxide (NO), while increasing the levels of parameters reflecting anti-oxidation, such as total antioxidant capacity (T-AOC) and glutathione (GSH), in MIRI-induced ischemic heart tissue. I3C pretreatment was also able to remarkably decrease the expression of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6) mRNA in ischemic heart tissue. These results demonstrate that administration of I3C protects the heart from MIRI through its anti-apoptotic, antioxidant, and anti-inflammatory effects.